NOS3 894G>T Polymorphism is Associated With Progression of Kidney Disease and Cardiovascular Morbidity in Type 2 Diabetic Patients: NOS3 as a Modifier Gene for Diabetic Nephropathy? - Katarína Kuricová; Veronika Tanhäuserová; Lukáš Pácal; Vendula Bartáková; Lucie Brožová; Jiří Jarkovský; Kateřina Kaňková (Karger Publishers, 2014)
Background/Aims: We have previously associated SNP 894G>T in the NOS3 gene with diabetic nephropathy (DN) using multi-locus analysis. Variant 894G>T has been widely studied as a DN susceptibility factor with contradictory results. In the present study we genotyped 894G>T in the cohort of prospectively followed type 2 diabetics with the aim to investigate its possible role in the progression of DN and development of morbidity and mortality associated with diabetes. Methods: 311 subjects with defined stage of DN were enrolled in the study and followed up for a median of 38 months. We considered three end-points: progression of DN, major cardiovascular event and all-cause mortality. Results: Considering baseline GFR, age at enrolment and diabetes duration as confounders, Cox regression analysis identified 894GT genotype as a risk factor for DN progression (HR = 1.843 [95% CI 1.088 - 3.119], P = 0.023) and 894TT genotype as a risk factor for major cardiovascular event (HR = 2.515 [95% CI 1.060 - 5.965], P = 0.036). Conclusion: We ascertained the significant effect of the NOS3 894G>T variant on DN progression and occurrence of major cardiovascular event in T2DM subjects. Based on these results NOS3 can be considered a modifier gene for DN.